Clinical and pharmacokinetic effects of regional or general anaesthesia on intravenous regional limb perfusion with amikacin in horses - Rubio-Martínez, L. M. (University of Pretoria, 2014)
Dissertation (MMedVet (Surgery Equine surgery))--University of Pretoria, 2012.